Nutritional support and nursing of a patient with mediastinal infection caused by esophageal foreign body (1例食管异物致纵隔感染患者的营养支持护理) - YANG Feili (杨非利); LI Zhen (李祯); LIU Jiao (刘娇) (Journal of International Translational Medicine Limited, 2024)
This paper summarized the nutritional support and nursing of a patient with mediastinal infection caused by esophageal foreign body. Based on the comprehensive evaluation of nutritional status of the patient, nutritionists, doctors and nurses jointly formulated a nutritional support treatment plan after operation, and carried out individualized nutritional support and other comprehensive nursing interventions such as oral care, enteral and parenteral nutrition, nasointestinal tube maintenance, and mediastinal infection control. The individualized nutritional support and comprehensive interventions were effective to improve the nutritional status, prevent complications and promote the recovery of the patient. (本文总结1例食管异物致纵隔感染的营养支持护理经验。通过积极评估患者营养状况, 由营养师、医师及护士共同制定营养支持治疗方案, 给予口腔护理、肠内场外营养护理、鼻肠管护理、纵隔感染护理全方位干预措施, 改善患者营养状况, 预防并发症, 促进早期康复。)